Test of Collagen-Chitosan Scaffold Activity on Healing Artificial Wounds on Rat (Rattus Norvegicus) Skin - Alfrit Rahmatu Retra; Muhammad Gunawan; Muhammad Bagas Fahriansyah; Cut Fatimah (JURNAL FARMASI DAN MAKANAN, 2024)
Wounds are disorders of the skin's protective function characterized by the loss of epithelial tissue continuity, either with or without damage to other tissues such as muscles, bones, and nerves. Scaffolds with porous structures play an important role in supporting cell function and helping the formation of new tissues or organs. The design of scaffolds for tissue engineering must meet several criteria, such as having a surface that supports cell adhesion, stimulates cell growth, and maintains differentiated cells. In this study, scaffolds were made using chitosan and collagen. Chitosan is known to stimulate cell proliferation, increase collagen formation, and accelerate epithelial cell regeneration in injured skin. Meanwhile, collagen is considered a very promising material in tissue engineering because of its biocompatible, biodegradable, and low antigenicity properties. The results showed that collagen-chitosan scaffolds with added glycerol were able to accelerate wound healing in mouse skin. On the 16th day, the wound healing process was already visible in the scaffold group with a ratio of 80:20:20, while on the 17th day there was no significant difference between the comparison group and the 70:30:20 (F2) and 80:20:20 (F3) scaffold groups. This shows that the better the combination of collagen and chitosan, the faster the wound healing process. Higher collagen concentrations in chitosan scaffolds have been shown to be effective in increasing regeneration and accelerating wound healing.